Sterically Controlled C–H Borylation and Silylation of (Hetero)arenes Using Pyrazolonaphthyridine Ligands - Kang, Eunsu; Jeong, Siyeon; Joo, Jung Min (Synthesis, 2025)
We have developed iridium-catalyzed C–H borylation and silylation reactions using pyrazolonaphthyridine (PzNPy) ligands. The readily tunable PzNPy system provides easy control of the ligand characteristics, enabling selective functionalization at the least hindered positions. With the new catalytic system, 1,4-disubstituted and multi-substituted toluene derivatives preferentially underwent borylation at benzylic positions, whereas 1,3-disubstituted arenes favored the least hindered sp2 positions. The Ir/PzNPy system also showed applicability in the C–H borylation of heteroarenes and metallocenes. Furthermore, increasing steric bulk near nitrogen atoms of ligand enabled C–H silylation of five-membered heteroarenes. These results expand the toolbox of bidentate nitrogen ligands for the development of iridium-catalyzed C–H functionalization reactions, suggesting the potential of tailorable PzNPy ligands to extend beyond their applications in palladium catalysis.
Keywords: Borylation; Silylation; Ligand; Iridium; C–H Activation